Burmannia tenella (Burmanniaceae) in Costa Rica: A new addition to the flora of Central America, with an overview of its geographic distribution - Álvarez Alcázar, Leonardo (2024)
Background and Aims: Burmannia tenella is a holo-mycoheterotrophic species widely distributed in the Amazon Biome. The objectives of this study are to report the presence of this species in Costa Rica, to present an overview of its geographic distribution, and to provide a key to the species of Burmannia in Mesoamerica. Methods: We review the distribution of Burmannia tenella based on literature, herbarium specimens and unequivocal photographic records, as well as recent collections from Costa Rica. Key results: Burmannia tenella is reported as new for Costa Rica, the first reported occurrence of this species west of the Andes. We review its geographic distribution and provide an updated key to the five known species of Burmannia in Mesoamerica. Apparent inconsistencies with the numbering of some of Richard Spruce’s herbarium collections (including the type of B. tenella) are briefly discussed. Conclusions: Given that all South American records of Burmannia tenella are from localities east of the Andes (the closest of which is 1170 km distant), the occurrence of this species in Central America represents a significant disjunction from its previously known geographical distribution.